2000
DOI: 10.1128/cdli.7.1.96-100.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine Differentially Modulates Chemokine Production by Mononuclear Cells from Normal Donors and Human Immunodeficiency Virus Type 1-Infected Patients

Abstract: Earlier studies have supported a significant role for cocaine in the susceptibility to and the progression of human immunodeficiency virus type 1 (HIV-1) infection. Recently, several unique HIV-1 entry coreceptors (e.g., CCR5 and CCR3) and a trio of HIV-1-specific suppressor chemokines, namely, RANTES (regulatedupon-activation T expressed and secreted), macrophage inflammatory protein 1␣ (MIP-1␣) and MIP-1␤, were identified. Although cocaine has been linked to the immunopathogenesis of HIV-1 infection, the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 21 publications
3
58
0
Order By: Relevance
“…Our data showing that morphine modulated expression of MIP-1␤ and CCR5 receptor are supported by several recently reported observations (47-49). Nair et al (47) recently reported that cocaine selectively down-regulates endogenous MIP-1␤ secretion and up-regulates CCR5 expression by adult peripheral blood monocytes, suggesting a mechanism by which cocaine increases susceptibility of peripheral blood monocytes to HIV infection. Morphine induces CCR5 expression in a human T-lymphoid cell line (CEMx174) (48).…”
Section: Discussionmentioning
confidence: 99%
“…Our data showing that morphine modulated expression of MIP-1␤ and CCR5 receptor are supported by several recently reported observations (47-49). Nair et al (47) recently reported that cocaine selectively down-regulates endogenous MIP-1␤ secretion and up-regulates CCR5 expression by adult peripheral blood monocytes, suggesting a mechanism by which cocaine increases susceptibility of peripheral blood monocytes to HIV infection. Morphine induces CCR5 expression in a human T-lymphoid cell line (CEMx174) (48).…”
Section: Discussionmentioning
confidence: 99%
“…Based upon the report of other investigators (Nair et al, 2000) that the stimulatory effect of cocaine on HIV-1 expression in PBMCs is associated with up-regulation of the viral entry chemokine coreceptor CCR5, we next investigated whether cocaine would also induce up-regulation of CCR5 in microglial cells, and if so, whether KOR ligands would inhibit this phenomenon. As shown in Fig.…”
Section: Effects Of Cocaine and Kor Ligands On Hiv-1 Expressionmentioning
confidence: 99%
“…Although several research groups have shown that cocaine potentiates HIV-1 expression in peripheral blood mononuclear cell (PBMC) cultures (Peterson et al, 1992;Bagasra and Pomerantz, 1993;Nair et al, 2000;Roth et al, 2002) by a mechanism that seems to involve up-regulation of the HIV-1 entry chemokine coreceptor CCR5 (Nair et al, 2000), little or nothing is known about the effects of cocaine on HIV-1 expression in microglial cells. Thus, we hypothesized in the present study that cocaine would potentiate viral expression in microglial cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…NHA were treated with and without cocaine-hydrochloride (Sigma-Aldrich, St. Louis MO); time and concentration used were based on previous studies that produced a maximum biological response without causing toxicity to the target cells (Nair et al, 2000;Nair et al, 2001;Nair et al, 2004;Nair et al, 2005). Cocaine was dissolved in sterile distilled water and was subsequently diluted in media to the required concentrations.…”
Section: Drug Treatmentmentioning
confidence: 99%